Comparison of the effects of lactated Ringer solution with and without hydroxyethyl starch fluid resuscitation on gut edema during severe splanchnic ischemia - S.M. Lobo; S.R.P. Orrico; M.M. Queiroz; L.M. Contrim; P.M. Cury (Brazilian Journal of Medical and Biological Research, 2008)
The type of fluid used during resuscitation may have an important impact on tissue edema. We evaluated the impact of two different regimens of fluid resuscitation on hemodynamics and on lung and intestinal edema during splanchnic hypoperfusion in rabbits. The study included 16 female New Zealand rabbits (2.9 to 3.3 kg body weight, aged 8 to 12 months) with splanchnic ischemia induced by ligation of the superior mesenteric artery. The animals were randomized into two experimental groups: group I (N = 9) received 12 mL·kg-1·h-1 lactated Ringer solution and 20 mL/kg 6% hydroxyethyl starch solution; group II (N = 7) received 36 mL·kg-1·h-1 lactated Ringer solution and 20 mL/kg 0.9% saline. A segment from the ileum was isolated to be perfused. A tonometric catheter was placed in a second gut segment. Superior mesenteric artery (Q SMA) and aortic (Qaorta) flows were measured using ultrasonic flow probes. After 4 h of fluid resuscitation, tissue specimens were immediately removed for estimations of gut and lung edema. There were no differences in global and regional perfusion variables, lung wet-to-dry weight ratios and oxygenation indices between groups. Gut wet-to-dry weight ratio was significantly lower in the crystalloid/colloid-treated group (4.9 ± 1.5) than in the crystalloid-treated group (7.3 ± 2.4) (P < 0.05). In this model of intestinal ischemia, fluid resuscitation with crystalloids caused more gut edema than a combination of crystalloids and colloids.